SOSIALISASI IDE BISNIS DAN OPTIMALISASI UMKM BAGI PEREMPUAN DI DESA PABEAN KECAMATAN SEDATI SIDOARJO - Ardhiani, Mutiara Rachma; Abimanyu, Bangkit; Akbar Febrianto, Muhammad; Fibertus Rande, Rikardus; Putri Nur Aisyiah, Emilia; Gymnastiar, Alfan; Ivah Umma, Neysa (Pusat Riset dan Inovasi Nasional, 2023)
In Indonesia, now it doesn't look at gender differences, meaning that in this era it's not only men who can make decisions in doing business, but women can make decisions and to pursue the businesses they own. Currently, single parent women can also have a business to meet family needs and participate actively in social life, government organizations or local organizations. Therefore the district government. Sidoarjo provides assistance through the Independent Women's Business Card (KURMA) program for single parent women to create and advance their businesses. With the implementation of this program, many women experience confusion in creating new UMKM and developing their businesses. The purpose of this socialization is to assist women in providing UMKM business ideas, reducing women's poverty, increasing women's income, increasing knowledge and knowledge along with the quality of human resources, especially women. Apart from that, our goal is to invite the women's community to become a community that is friendly to banks and the economy.